BUDAYA HIDUP SEHAT (Sebuah Tinjauan Bioetis) - William Chang (Institut Filsafat dan Teknologi Kreatif Ledalero, 2015)
This paper intends to highlight HIV and AIDS in the context of a culture of healthy living. The initial analysis underlines health care as a key responsibility of each individual. Thus, neglect of this responsibility invites a critique of our way of life which is itself sick. The reasons for and results from HIV and AIDS cannot be ignored. One important step to anticipate and overcome the HIV infection and AIDS sickness is to form an underlying positive attitude and establish a culture of healthy living, which supports a healthy lifestyle, is responsible, and sustains the value of life and healthy living. Kata-kata kunci: HIV, AIDS, perawatan, kesehatan, budaya, sehat, sikap, positif.